Proteomic analysis of trans-hemispheric motor cortex reorganization following contralateral C(7) nerve transfer - Yuan, Yin (Neural Regen Res, 2018)
Nerve transfer is the most common treatment for total brachial plexus avulsion injury. After nerve transfer, the movement of the injured limb may be activated by certain movements of the healthy limb at the early stage of recovery, i.e., trans-hemispheric reorganization. Previous studies have focused on functional magnetic resonance imaging and changes in brain-derived neurotrophic factor and growth associated protein 43, but there have been no proteomics studies. In this study, we designed a rat model of total brachial plexus avulsion injury involving contralateral C(7) nerve transfer. Isobaric tags for relative and absolute quantitation and western blot assay were then used to screen differentially expressed proteins in bilateral motor cortices. We found that most differentially expressed proteins in both cortices of upper limb were associated with nervous system development and function (including neuron differentiation and development, axonogenesis, and guidance), microtubule and cytoskeleton organization, synapse plasticity, and transmission of nerve impulses. Two key differentially expressed proteins, neurofilament light (NFL) and Thy-1, were identified. In contralateral cortex, the NFL level was upregulated 2 weeks after transfer and downregulated at 1 and 5 months. The Thy-1 level was upregulated from 1 to 5 months. In the affected cortex, the NFL level increased gradually from 1 to 5 months. Western blot results of key differentially expressed proteins were consistent with the proteomic findings. These results indicate that NFL and Thy-1 play an important role in trans-hemispheric organization following total brachial plexus root avulsion and contralateral C(7) nerve transfer.